Actions and beliefs: estimating distribution-based preferences using a large scale experiment with probability questions on expectations - Charles Bellemare; Sabine Kröger; Arthur van Soest (Institute for the Study of Labor (IZA), 2005)
We combine the choice data of proposers and responders in the ultimatum game, their expectations elicited in the form of subjective probability questions, and the choice data of proposers (dictators) in a dictator game to estimate a structural model of decision making under uncertainty. We use a large and representative sample of subjects drawn from the Dutch population. Our results indicate that there is considerable heterogeneity in preferences for equity in the population. Changes in preferences have an important impact on decisions of dictators in the dictator game and responders in the ultimatum game, but a smaller impact on decisions of proposers in the ultimatum game, a result due to proposer's subjective expectations about responders' decisions. The model which uses subjective data on expectations has better predictive power and lower noise level than a model which assumes that players have rational expectations.
Keywords: C93; D63; D84; 330; ultimatum game; inequity aversion; subjective expectations